A Mediterranean diet does not alter plasma trimethylamine N-oxide concentrations in healthy adults at risk for colon cancer. Issue 4 (2nd April 2019) - Griffin, Laura E.; Djuric, Zora; Angiletta, Chris J.; Mitchell, Cassie M.; Baugh, Mary E.; Davy, Kevin P.; Neilson, Andrew P.
Abstract : A Mediterranean diet does not reduce circulating TMAO, a metabolite that is associated with chronic disease risks. Abstract : An elevated circulating level of trimethylamine N -oxide (TMAO) has been identified as a risk factor for numerous diseases, including cardiovascular disease (CVD) and colon cancer. TMAO is formed from trimethylamine (TMA)-precursors such as choline via the combined action of the gut microbiota and liver. We conducted a Mediterranean diet intervention that increased intakes of fiber and changed intakes of many other foods containing fat to increase the relative amount of mono-unsaturated fats in the diet. The Mediterranean diet is associated with reduced risks of chronic diseases and might counteract the pro-inflammatory effects of increased TMAO formation. Therefore, the purpose of this study was to determine if the Mediterranean diet would reduce TMAO concentrations. Fasting TMAO concentrations were measured before and after six-months of dietary intervention in 115 healthy people at increased risk for colon cancer. No significant changes in plasma TMAO or in the ratios of TMAO to precursor compounds were found in either the Mediterranean group or the comparison group that followed a Healthy Eating diet. TMAO concentrations exhibited positive correlations with age and markers of metabolic health. TMAO concentrations were not associated with circulating cytokines, but the relative abundance of Akkermansia mucinophilia in colon biopsies was modestly and inversely correlated with baseline TMAO, choline, and betaine serum concentrations. These results suggest that broad dietary pattern intervention over six months may not be sufficient for reducing TMAO concentrations in an otherwise healthy population. Disruption of the conversion of dietary TMA to TMAO should be the focus of future studies.